(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article provides a detailed comparative analysis of written speech from two different historical periods by examining a letter written in the mid-20th century and modern SMS messages. The classical emotional expressiveness, lexical richness, and the synthesis of colloquial and literary styles found in traditional letters are compared with abbreviations, emojis, and informal writing styles typical of contemporary virtual communication tools. Particular attention is paid to linguistic economy, sociocultural references, gender-specific speech characteristics, and the expression of emotions through symbols such as emojis and punctuation marks.